2017
DOI: 10.1371/journal.pone.0181008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of peak oxygen uptake during handcycling: Test-retest reliability and comparison of a ramp-incremented and perceptually-regulated exercise test

Abstract: PurposeTo examine the reliability of a perceptually-regulated maximal exercise test (PRETmax) to measure peak oxygen uptake () during handcycle exercise and to compare peak responses to those derived from a ramp-incremented protocol (RAMP).MethodsTwenty recreationally active individuals (14 male, 6 female) completed four trials across a 2-week period, using a randomised, counterbalanced design. Participants completed two RAMP protocols (20 W·min-1) in week 1, followed by two PRETmax in week 2, or vice versa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
2
12
0
1
Order By: Relevance
“…These findings corroborate previous research that has found a perceptual signal dominance of RPEP over RPEC in untrained AB persons performing arm crank, 21 handcycle, 22 and wheelchair propulsion 7,23,24 exercise. Similar investigations into the differentiated RPE of CSCI have proven equivocal.…”
Section: Discussionsupporting
confidence: 92%
“…These findings corroborate previous research that has found a perceptual signal dominance of RPEP over RPEC in untrained AB persons performing arm crank, 21 handcycle, 22 and wheelchair propulsion 7,23,24 exercise. Similar investigations into the differentiated RPE of CSCI have proven equivocal.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of high relative reliability of physiological parameters of the three upper-body poling tests, reflected by high ICCs, are in line with several previous studies. Three minutes closed-end and incremental arm crank ergometry tests displayed similar ICCs in not specifically upper-body trained able-bodied participants (Leicht et al, 2009 ; Flueck et al, 2015 ; Hutchinson et al, 2017 ) as well as incremental wheelchair ergometry or treadmill tests in athletes with different disabilities (Bhambhani et al, 1991 ; Leicht et al, 2013 ). The current data shows that the ranks of the participants remain stable from test day 1 to test day 2 also during upper-body poling.…”
Section: Discussionmentioning
confidence: 95%
“…Exercise testing in a sitting position is relevant for determining upper-body physiological capacities and monitoring training progression in both Paralympic sitting athletes as well as able-bodied athletes involved in an upper-body sport. Various test protocols have been used to determine peak oxygen uptake (VO 2peak ) in upper-body modes, with the most common test procedure comprising incremental increases in workload until voluntary exhaustion (Bar-Or and Zwiren, 1975 ; Bhambhani et al, 1991 ; Leicht et al, 2009 , 2013 ; Hutchinson et al, 2017 ). In addition, a 3-min self-paced closed-end test is a common procedure to assess VO 2peak in upper-body modes (Skovereng et al, 2013 ; Flueck et al, 2015 ; Hegge et al, 2015a , b ; Baumgart and Sandbakk, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, training status still seems to be one of the strongest determinants of handcycling aerobic capacity; this has been shown in studies comparing handcyclists of varying training histories. 28,35 Of the available literature, to the authors' knowledge, Hutchinson et al 42 was the only study that has used a | STEPHENSON ET al. Note: Values are mean ± standard deviation, where appropriate.…”
Section: Laboratory Testing: Aerobic Capacitymentioning
confidence: 99%
“…Modern ergometers, such as the commonly used Cyclus II, allow PO, cadence, and gearing to be controlled, measured accurately and reliably and also allow several exercise protocols, such as incremental exercise tests, TTs, and sprints, to be conducted in the users' own handbike. 42 However, as the ergometers are fixed, factors such as rolling resistance and air resistance are estimated and the steering/stabilization mechanisms of handcycling are removed. 13 A smaller number of studies have utilized treadmills to assess the physiology of handcycling.…”
Section: Simulating Performancementioning
confidence: 99%